Whither Mental Health Policy-Where Does It Come from and Does It Go Anywhere Useful?; Comment on "Cross-National Diffusion of Mental Health Policy" - Rachel Jenkins (Kerman University of Medical Sciences, 2015)
Factors influencing cross-national diffusion of mental health policy are important to understand but complex to research. This commentary discusses Shen's research study on cross-national diffusion of mental health policy; examines the extent to which the three questions researched by Shen (whether countries are more likely to have a mental health policy (a) the earlier a country becomes a member of World Health Organization (WHO), (b) the more international aid a country receives, and (c) the more neighbouring countries already have a mental health policy) are in fact able to assess WHO's impact on cross-national diffusion of mental health policy. The commentary then suggests a range of more specific questions which may be used to further elucidate the impact of WHO on an individual country, and considers the relative value of published mental health policy compared with the integration of mental health into national health sector strategies and other sector reforms, and concludes with a call for more integration of mental health across all WHO activities at international, regional and country levels.